2019
DOI: 10.1590/1980-549720190007.supl.1
|View full text |Cite
|
Sign up to set email alerts
|

Exploratory spatial analysis of HBV cases in Brazil between 2005 and 2017

Abstract: Objective: To analyze the pattern of spatial distribution of hepatitis B virus (HBV) cases and the mortality attributed to this disease throughout the Brazilian territory, in 2005, 2016 and 2017. Methods: This is an ecological study of spatial analysis, using data from the Information System for Notifiable Diseases and the Brazilian Mortality Information System. HBV detection and mortality rates were analyzed. The spatial analysis from 2005 to 2017 was held through the Global Moran’s Index (I) for global data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 15 publications
0
8
0
6
Order By: Relevance
“…Each type represents different practical significance, indicating the spatial heterogeneity between adjacent provinces. A positive Moran's I value implies that the human resources in rehabilitation institutions were spatially clustered, and the spatial cluster types include high-high clusters (HH, high SRID, PD or MPD in a high SRID, PD or MPD neighborhood) and low-low clusters (LL, low SRID, PD or MPD in a low SRID, PD or MPD neighborhood); A negative Moran's I value implies that the human resources in rehabilitation institutions are staggered and evenly distributed (they are different from the surrounding zones) and include high-low outliers (HL, high SRID, PD or MPD in a low SRID, PD or MPD neighborhood) and low-high outliers (LH, low SRID, PD or MPD in a high SRID, PD or MPD neighborhood); Additionally, the NG type shows random distribution ( 27 ).…”
Section: Methodsmentioning
confidence: 99%
“…Each type represents different practical significance, indicating the spatial heterogeneity between adjacent provinces. A positive Moran's I value implies that the human resources in rehabilitation institutions were spatially clustered, and the spatial cluster types include high-high clusters (HH, high SRID, PD or MPD in a high SRID, PD or MPD neighborhood) and low-low clusters (LL, low SRID, PD or MPD in a low SRID, PD or MPD neighborhood); A negative Moran's I value implies that the human resources in rehabilitation institutions are staggered and evenly distributed (they are different from the surrounding zones) and include high-low outliers (HL, high SRID, PD or MPD in a low SRID, PD or MPD neighborhood) and low-high outliers (LH, low SRID, PD or MPD in a high SRID, PD or MPD neighborhood); Additionally, the NG type shows random distribution ( 27 ).…”
Section: Methodsmentioning
confidence: 99%
“…The use of this approach in studies concerning spatiotemporal analysis of infectious neglected diseases has increased in recent years. Using univariate GMI and LMI have shown that several diseases present cluster distribution patterns including hotspots (Machado et al, 2017;Osei & Stein, 2017;Mandal et al, 2018;Salimi et al, 2018;Tewara et al, 2018;Alene et al, 2019;Nuñez-González et al, 2019;Okunlola et al, 2019;Vivaldini et al, 2019). Bivariate GMI and LMI have only been applied to evaluate spatial autocorrelation and clusters et al, 2019) reported cluster distributions and hotspots throughout the country.…”
Section: Articlementioning
confidence: 99%
“…In Brazil, the general prevalence of the surface antigen of HBV (HBsAg) is less than 2%; however, this rate may vary according to the geographic area. The Amazon region (northern Brazil) is considered a highly endemic area when compared to other Brazilian regions 5,6 . Regarding HCV, it is estimated that 1%–2% of the Brazilian population has active infection with the virus 6 .…”
Section: Introductionmentioning
confidence: 99%
“…The Amazon region (northern Brazil) is considered a highly endemic area when compared to other Brazilian regions. 5,6 Regarding HCV, it is estimated that 1%-2% of the Brazilian population has active infection with the virus. 6 In the state of Pará (northern Brazil), the prevalence of anti-HCV antibodies among blood donors is estimated at around 0.2%.…”
Section: Introductionmentioning
confidence: 99%